Alternatives from the Global South to Confront Social and Environmental Crises - Barkin, David (2023)
Dominant theories in the social sciences support the developing forces of colonialism and imperialism, as well as the consolidation of a "global market," giving rise to ethnocide and environmental devastation on a planetary scale. Instead of denouncing them, it is appropriate to offer another analytical framework to approach an understanding of the peoples who are resisting this dispossession with "very different" visions. These societies are building communal forms of life, rooted in other cosmogonies, recognizing the value of the different contributions of genders, the richness of generational differences, the capacities to self-govern and flourish, the importance of community, without underestimating the meaning of individuality. To address their contributions, a new epistemology is required: Radical Ecological Economics. We begin with La milpa mesoamericana as an example of the profound differences between productivist approaches and those based on the intimate relationship between society and nature. Communality guides deliberate strategies to forge solidarity and well-being with important bonds of mutual support between societies that are continuously incorporating innovations that strengthen them, always aware of the obligation to take care of their environments, designing appropriate socio-ecological metabolisms.